Development of a laser ablation process model and a disposable 3D-printed tool head for weakening thick steel sheets for the deflagration of hazardous substances. (August 2019) - Kaierle, Stefan; Overmeyer, Ludger; Hoff, Christian; Meier, Oliver; Hermsdorf, Jörg
Abstract: So far, laser processes for the defined weakening of metals have been investigated only in wall thickness ranges of a few millimeters. In the case considered, the sheaths of UXOs (4–25 mm) are to be weakened in order to reduce danger. The developed model for the melt-ablation process with a 2 kW solid-state laser enables the defined weakening of steel sheets of up to 15 mm. It is ensured that a critical temperature of 300 °C on the underside of the material is not exceeded. In accordance with the process requirements, a cost-effective 3D-printed disposable process head is manufactured and verified with regard to the developed model.